Modelagem computacional da reação do íon amideto com formiato de metila em fase gasosa - Vieira Neto, José Carlos (2022)
This study computationally addresses the modeling of the chemical reaction between the amide ion (NH2-) and the methyl formate molecule (HCOOCH3) in the gas phase. Experimental results suggest that the interaction between the amide ion and the neutral methyl formate molecule can occur by four mechanisms in the gas phase, which are: (1) methyl proton abstraction mechanism (AP-2) being or more favored and raising to formation of two products HCO2CH2-, and NH3; (2) Riveros mechanism (AP-1) or second most favored channel and causes α-elimination of the CO molecule, formation of NH3 and CH3O- ion; (3) (BAC2) also called because it represents an attack on the acyl carbon, or a third favoring mechanism by which the products HCONH- and CH3OH or HCONH2 and CH3O- can be formed; (4) second-order nucleophilic substitution (SN2), from the attack of the amidete to the methyl carbon of methyl formate, leading to the formation of two products CH3NH2 and HCO2-. In order to characterize the structures of minimums and obtain their respective energies, the theory level MP2/6-311++G(d,p) was undertaken, subsequently aiming at a refinement of the energies used at the CCSD(T) level as the basis functions aug-cc-pVnZ, with n=(D and Z) used for extrapolating the energies for a complete basis set (CBS) with the quais forams constructed the potential energy profiles. As the main modeling results for the NH2- + HCOOCH3 reaction, the RRKM (Rice-Ramsperger-Kassel-Marcus) calculations suggest that the distribution of two products two mechanisms SN2:BAC2:AP corresponds to 7%:49%:44%, indicating that the CH3O- ion can also be formed by the BAC2 mechanism. The addition of a water molecule to the reaction, NH2–(H2O) + HCOOCH3, revealed that a single water molecule raised the activation barrier energies of two transition states, especially for the SN2 mechanism, making it higher than two energy reagents making it impossible to observe two products of such a mechanism. The AP-1, AP-2 and BAC2 mechanisms maintain two reagent energy below, therefore, the total fragmentation of two products for the proton abstraction mechanisms will become endothermic, as well as the kinetic calculations will reveal that the mechanism of Riveros is favored over the others with about 76% in terms of the BAC2 mechanism, second most favored, presenting a performance of 24% in the AP-2 and SN2 mechanisms, 0,2% and 0%, respectively. The disfavor of the BAC2 mechanism in relation to the Riveros mechanism is attributed to the movement of water proton abstraction carried out by amide before the attack on the acyl carbon, while the Riveros mechanism occurs freely and therefore shows higher yield.